Orçamentos municipais em saúde e desempenho dos indicadores de saúde : uma análise para a década 2005-2014 - Tonetto, Jorge Luis (2017)
This research was directed at health economics, seeking to verify if municipal public health expenditures have an influence on the variation of the health indicators of each municipality, specifically in the indicators IFDM-Health (Firjan Index of Municipal Development) and Potential Years of Lost Life. First, there was a broad review of the national and international literature, with emphasis on the regulatory framework, health expenditures, financing models and efficiency. The period analyzed was from 2005 to 2014 for the Potential Years of Lost Lifeand from 2005 to 2013 for the IFDM-Health. All Brazilian municipalities that had available indicators were analyzed, and the Potential Years of Lost Lifewere calculated for each municipality per year, with the limit of 70 years as a potential life. The expenditures data of the municipalities were extracted from the National Treasury Secretariat and were inflated by the IPCA until 2014. The databases of IBGE, Datasus and SNIS were also used. This basis was adequate to its nomenclature and worked to be used in an econometric program for panel analysis. Four models were developed, two for each dependent variable, differentiated by the use of the health function and alternatively by the sub-functions of basic care and hospital care. The results pointed in different directions. For all models, analyzing the periods of each management over time, suggests an improvement in efficiency. Population size has significance for the variable Potential Years of Lost Life, and the municipal expenditure function was also significant in the quadratic and cubic forms, and only the basic care subfunction showed to be relevant, allowing an optimal point to be determined, from where the efficiency process started. For the IFDM-Health, the variable physicians was significant and the signal as expected. The municipal expenditures on the health function were also relevant in the quadratic form, indicating a point where it becomes inefficient. In health subfunctions expenditures, it was possible to find an optimization point for both.